Does corporate governance make financial reports better, or just better for equity investors? - Segal, Dan (Institutional Knowledge at Singapore Management University, 2014)
Financial reports should provide useful information to both shareholders and creditors, according to U.S. accounting principles. However, directors of corporations have fiduciary duties only toward equity holders, and those fiduciary duties normally do not extend to the interests of creditors. We examine whether this slant in corporate governance biases financial reports in favor of equity investors, and in particular leads to a downward bias in reported debt that can hurt creditors. We focus on firms’ decision to issue structured debt securities that are classified as equity in financial reports and can circumvent debt covenants. We find that when the local legal regime requires directors to consider creditors’ interests, firms are less likely to use such structured transactions, particularly if the board of directors of the firm is independent. Our results suggest that when corporate governance is designed to protect only equity holders, firms’ financial reports serve equity holders’ interests at the expense of other stakeholders